Peran Sistem Informasi dalam Pengelolaan Supply Chain Management dan Aplikasinya di PD. Agro Selaparang Lombok Timur - Widia Febriana; Ika Nurul Qamari; Nuryakin Nuryakin (Target : Jurnal Manajemen Bisnis, 2021)
Agro Selaparang Lombok Timur is a company engaged in supply chain management : drinking water during the period (AMDK), animal feed, iodized salt, and block ice products, as for the objectives of this study, among others: 1) Knowing the supply chain management structure in PD. Agro Selaparang, 2) Analyze information systems (information communication technology, expert support, electronic business processes), used in dealing with suppliers, 3) Identifying how exposure is information systems in supply chain management, problems that occur currently in PD. Agro Selaparang, East Lombok, is a government obstacle such as lack of sanitarian personnel, allocation of funds, inspection of ice block product samples, feed, iodized salt and drinking water in a low AGRO period (AMDK), a burden double work. There are no strict sanctions and a lack of cooperation between sectors, too affects the quality of products that do not meet the requirements, so it affects on the product management process, besides the lack of feed stock due to the company as a distributor. Based on the problems that occur, the role of the system is needed information with supply chain management. The purpose of information systems can be help supply chain management in the company. The research was carried out with a qualitative approach through direct observation, in-depth interviews and documentation. The results showed that in the supply chain management process PD. Agro Selaparang East Lombok uses an integrated information system and one doors, through financial information systems.